2017
DOI: 10.1093/cid/cix145
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pneumococcal DNA in Blood by Polymerase Chain Reaction for Diagnosing Pneumococcal Pneumonia in Young Children From Low- and Middle-Income Countries

Abstract: Background.We investigated the performance of polymerase chain reaction (PCR) on blood in the diagnosis of pneumococcal pneumonia among children from 7 low- and middle-income countries.Methods.We tested blood by PCR for the pneumococcal autolysin gene in children aged 1–59 months in the Pneumonia Etiology Research for Child Health (PERCH) study. Children had World Health Organization–defined severe or very severe pneumonia or were age-frequency–matched community controls. Additionally, we tested blood from gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 24 publications
3
47
0
Order By: Relevance
“…The relative paucity of pneumococcus in bacterial culture despite the absence of a vaccination programme during the study period indirectly suggests that the pneumococcal disease burden was lower than expected. This was also emphasised by the culture data in the Community Acquired Pneumonia Etiology Study from our institution and the Pneumonia Etiology Research for Child Health data from sites in Bangladesh and Thailand . However, a study in South African children reported that polymerase chain reaction analysis of pleural fluid dramatically increased the yield of pneumococcus compared to just cultures .…”
Section: Discussionmentioning
confidence: 83%
“…The relative paucity of pneumococcus in bacterial culture despite the absence of a vaccination programme during the study period indirectly suggests that the pneumococcal disease burden was lower than expected. This was also emphasised by the culture data in the Community Acquired Pneumonia Etiology Study from our institution and the Pneumonia Etiology Research for Child Health data from sites in Bangladesh and Thailand . However, a study in South African children reported that polymerase chain reaction analysis of pleural fluid dramatically increased the yield of pneumococcus compared to just cultures .…”
Section: Discussionmentioning
confidence: 83%
“…A study among children and adults hospitalized with acute LRTI in South Africa found that invasive pneumococcal pneumonia was associated with increased colonization density; cases with density >1000 copies/mL had 18 times greater odds of invasive pneumococcal pneumonia than colonized cases with density <1000 copies/mL [10]. The South African study defined invasive pneumococcal pneumonia by detection of S. pneumoniae by PCR in the blood, a diagnostic not used in our study owing to poor specificity [31,32]. We found that the best-performing threshold (6.9 log 10 [10 6.9 ] copies/mL) was much higher than that suggested by the South African study, but comparison of density thresholds between studies is limited by methodologic differences.…”
Section: Discussionmentioning
confidence: 88%
“…[107][108][109] However recent results from the multicenter Pneumonia Etiology Research for Child Health (PERCH) study showed both poor sensitivity (64%; 36/56 microbiologically confirmed pneumococcal pneumonia cases were PCR positive) and specificity (5.5%; 273/4987 of non-pneumonia controls were PCR positive). 110 These results illustrate the need for Reducing contamination of samples Samples that are less likely to be contaminated by upper respiratory flora may be less prone to problems of interpretation. Bronchoscopy with bronchoalveolar lavage (BAL) or aspirate may provide a representative sample from the lower respiratory tract but it is invasive and requires specialized skill and sedation of the child.…”
Section: Value Of Different Specimen Types and Associated Diagnostic mentioning
confidence: 90%
“…Serological testing of blood specimens may be useful for epidemiological studies of the cause of pneumonia, where comparison of acute and convalescent titers may help identify the causative agent, [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] although the diagnostic value of a single specimen collected in the acute phase of the illness is generally limited. Pertussis serology may be a useful complementary diagnostic tool in older children and during the later phases of illness.…”
Section: Emerging Diagnosticsmentioning
confidence: 99%